2020
DOI: 10.1039/d0ta05787h
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-free efficient organic solar cells via an alkylbenzene side-chain strategy of small-molecule electron acceptors

Abstract: Research on alkylbenzene side-chain engineering of acceptors, which can affect the crystallinity of molecule and packing orientations of the blend films, has deeply promoted the development of organic solar cells...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The structural versatility of organic building blocks allows the design of countless organic materials. [53][54][55][56][57][58] It is not possible to explore this large chemical space. Therefore, it is essential to dene the chemical space that needs to be explored.…”
Section: Designing New Compoundsmentioning
confidence: 99%
“…The structural versatility of organic building blocks allows the design of countless organic materials. [53][54][55][56][57][58] It is not possible to explore this large chemical space. Therefore, it is essential to dene the chemical space that needs to be explored.…”
Section: Designing New Compoundsmentioning
confidence: 99%
“…Regarding the chemical structure tailoring, it has been well recognized that the subtle structural modification of NFAs can bring dramatic changes toward light absorption, energy levels, and molecular aggregation to impact device performance. The modification of NFA chemical structure can be executed through side chains, backbones, and end groups. For example, by grafting branched alkyl chains on the pyrrole motif of the Y6 NFA molecule to receive N3, Yan et al reported the enhancement of PCE from 15.2 to 15.98% for a single-junction PM6:NFA binary OSC . By shortening the n -undecyl (C11) to n -nonyl (C9) alkyl chain at the edge of the central donating core to receive BTP-eC9, Hou et al reported enhanced PCE from 16.9 to 17.8% .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the PBTPBD‐50 has superior miscibility with IT‐4F when processed with o ‐xylene. [ 37–40 ] In contrast, the thermally annealed PM6:IT‐4F blended film showed strong aggregation with a R q roughness of 3.32 nm, which are unfavorable for charge transport and collection. The unfavorable morphological change in the thermally annealed PM6:IT‐4F blended film accounts for the poor long‐term thermal stability of the PM6‐based PSC.…”
Section: Resultsmentioning
confidence: 99%